FACTORS AFFECTING THE PERFORMANCE OF FINANCIAL ADMINISTRATION OFFICER OF REGIONAL APPARATUS ORGANIZATION (FAO-RAO) IN THE ENVIRONMENT OF THE ACEH SOUTHEAST REGENCY GOVERNMENT USING INFORMATION TECHNOLOGY AS A MODERATING VARIABLE - Handayana, Sidriana (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to: (1) analyse the dependent variable, namely the performance of financial administration officer of the regional apparatus organization(FAO-RAO) in the Southeast Aceh Regency Government by examining the independent variables in this study, namely: understanding of the accounting system, understanding of regional financial management, education and training, work experience, communication, motivation, mental attitude and organizational commitment. The following objectives are: (2) analysing moderating variables, namely the use of information technology which moderates the relationship between understanding the accounting system, understanding regional financial management, education and training, work experience, communication, motivation, mental attitude and organizational commitment with the performance of the Financial Administration Officer of the Regional Apparatus Organization . The population in this study is the Financial Management Officer, all populations are used as research samples. Data from this study are primary data consisting of questionnaires given directly to respondents and then collected on time. The data will be tried by the writer through multiple linear regression.